PENGARUH LEVERAGE, TAX AVOIDANCE, DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN DENGAN KOMISARIS INDEPENDEN SEBAGAI MODERASI - Jonathan Kurniawan; Ngadiman (Fakultas Ekonomi Universitas Tarumanagara, 2024)
The purpose of this study was to determine the relationship of leverage, tax avoidance, and firm size to firm value byusing independent commissioners as moderation. The companies studied were manufacturing companies in the foodand beverage sub-sector listed on the IDX, for the period 2018-2021. The results showed that the three independentvariables had no significant effect on firm value, and the independent commissioner variable could only moderatethe leverage and firm size variables.